No turning back : artworks from the torch : Deakin University "Pop Up" Gallery Deakin Downtown 29 May to 14 July 2017. - Morris, Kent; Deakin University Art Gallery (Burwood, [Victoria] : Deakin University Art Gallery, 2017)
Features works by 11 Indigenous artists who participated in The Torch's Indigenous Arts in Prison and Community program.
Exhibition catalogue.
Caption title.
Kent Morris (Barkindji), chief executive officer.
Do Not Withdraw
Keywords: Prisoners as artists -- 21st century -- Exhibitions; Art, Aboriginal Australian -- 21st century -- Exhibitions; Painting, Australian -- 21st century -- Exhibitions; Prisoners as artists -- Exhibitions; Australian